1997
DOI: 10.1099/00222615-46-9-785
|View full text |Cite
|
Sign up to set email alerts
|

Value of surveillance cultures in a bone marrow transplantation unit

Abstract: Because of the increased risk of infection with the associated diagnostic and therapeutic problems in bone marrow transplantation (BMT) patients, the usefulness of surveillance cultures (SC) at the BMT department of the National Institute of Haematology, Blood Transfusion, Transplantation and Immunology, Budapest, was reviewed. Between January 1992 and May 1995, 26 BMT operations were performed; 13 patients had 23 febrile espisodes. In 12 of these episodes infection was clinically documented; however, SC of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
1
11
0
3
Order By: Relevance
“…Rigby et al [16] reported that 3 of 43 positive blood cultures in neutropenic children which yielded organisms, when repeated prior to starting antibiotics were sterile, suggesting that these positive cultures represented colonization rather than infection. Czirok et al [17] found that in 14 episodes of fever in 23 HSCT patients , surveillance cultures yielded bacteria identical with those in clinical blood cultures in only one episode and in the remaining three documented BSIs the identified bacteria isolated by surveillance cultures was not the same as the bacteria identified by clinical blood cultures. They concluded that surveillance blood cultures were of limited value in predicting infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rigby et al [16] reported that 3 of 43 positive blood cultures in neutropenic children which yielded organisms, when repeated prior to starting antibiotics were sterile, suggesting that these positive cultures represented colonization rather than infection. Czirok et al [17] found that in 14 episodes of fever in 23 HSCT patients , surveillance cultures yielded bacteria identical with those in clinical blood cultures in only one episode and in the remaining three documented BSIs the identified bacteria isolated by surveillance cultures was not the same as the bacteria identified by clinical blood cultures. They concluded that surveillance blood cultures were of limited value in predicting infection.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, some experts have recommended surveillance blood cultures to detect occult bacteremia [12]. Previous studies regarding the utility of surveillance blood cultures in patients undergoing hematopoietic stem cell transplantation (HSCT) are scarce with small numbers of patients, and describe specific subgroups of patients in relation to the type of transplant or the patients’ age [13-17]. Moreover, these studies have come to differing conclusions [10-13].…”
Section: Introductionmentioning
confidence: 99%
“…Estes dados são semelhantes aos descritos por Czirók e cols. que estudaram culturas de vigilância em 26 pacientes submetidos ao TMO e observaram maior incidência de bactérias gram-positivas, sendo pele, orofaringe, glande e vagina os locais de maior colonização (5).…”
Section: Materials Coletado Gram-positivos (%) Gram-negativos (%)unclassified
“…Riley et al estudaram 48 pacientes que realizaram TMO e questionaram o papel das culturas de vigilância ao observarem baixa sensibilidade (38%), especificidade (25%), valor preditivo positivo (20%) e valor preditivo negativo (20%) em relação ao desenvolvimento das infecções documentadas no grupo (3). Baixa correlação entre culturas de vigilância positivas e infecções clinicamente documentadas também foi observada por outros autores (5). Entretanto, as culturas de vigilância podem ser úteis na investigação dos efeitos dos tratamentos profiláticos na seleção de germes resistentes, e auxiliar o estudo da epidemiologia da colonização nos pacientes netropênicos.…”
Section: Materials Coletado Gram-positivos (%) Gram-negativos (%)unclassified
“…Patients who are colonized with multidrug-resistant bacteria may serve as a source of later infection in the same patient and also as infection risk for neighboring patients if not isolated. [5] Surveillance cultures may be helpful in identifying these multidrug-resistant bacteria, which may have a bearing on further patient management.…”
mentioning
confidence: 99%